Analysis on the impact process parameters on tensile strength using 3d printer repetier-host software - Sukindar, Nor Aiman; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B. T. Hang Tuah; Jaafar, Che Nor Aiza; Ismail, Mohd Idris Shah (Asian Research Publishing Network (ARPN), 2017)
RepRap (Replicating Rapid Prototyper) is an open-source 3D printer which current revolution from rapid prototyping technology. The technology has become well-known to the public and starting to widely commercialize in the market. The low cost and flexibility of the open-source 3D printer become the alternative for making three-dimensional parts. The advantage of using this technology is that the user has a complete freedom of controlling the process parameters of the fabricate product. Despite of being a low-cost 3D machine, there is no extensive study of the performance on this technology. This paper investigates the impact on process parameters for tensile strength using polylactic acid (PLA) material. Parts were printed using newly developed open-source 3D printer with Repetier-Host software by manipulating three parameters which were layer thickness, shell thickness and printing speed. The printed parts were tested under tensile test machine and the analysis from ANOVA shows that the shell thickness contributes higher significant impact on tensile strength.